Enhanced room-temperature ethanol sensing performance of porous MoO3/V0.13Mo0.87O2.935 heterostructures self-assembled with 2D nanosheets. Issue 20 (11th May 2021) - Guo, Jia; Li, Hang; Chu, Shushu; Zhang, Qi; Lin, Ziqiong; Ma, Qian
Abstract : Porous MoO3 /V0.13 Mo0.87 O2.935 heterostructures self-assembled with 2D nanosheets have been primarily prepared by a facile method for effectively detecting ethanol at room temperature. Abstract : Porous MoO3 /V0.13 Mo0.87 O2.935 heterostructures self-assembled with 2D nanosheets have been primarily prepared by a facile method for effectively detecting ethanol at room temperature. The V0.13 Mo0.87 O2.935 phase contributes to modified microspheres and improved surface/interface structures. The enhanced sensing mechanism benefits from the effects of MoO3 –V0.13 Mo0.87 O2.935 heterojunctions and tunable microstructure.